INFLUENCE OF STRATEGIC E-PROCUREMENT PRACTICE ON PERFORMANCE OF DEVOLVED SYSTEMS OF GOVERNMENT IN KENYA - Chepng'etich, Carren; Waiganjo, Esther; Ismail, Noor (International Journal of Supply Chain Management, 2020)
Purpose: The purpose of this study was to establish the influence of strategic e-procurement practice on performance of Devolved systems of government in Kenya. Methodology: The study adopted cross-sectional survey design using both quantitative and qualitative approaches. The target population was all the 47 devolved systems of government. The sample size was the 10 counties namely; Garissa, Kisii, Nyamira, Narok, Marsabit, Murang'a, Bomet, Nairobi, Kiambu and Homa Bay specifically employees working under finance and procurement department. The study adopted stratified random sampling to pick 186 respondents from finance and procurement department. Data was collected by using questionnaires Descriptive and inferential statistics was used aided by Statistical Packages for Social Sciences version 24 to compute percentages of respondents' answers. Hypothesis testing was carried using multiple regression analysis and standard F tests. The results were presented using tables. Results: The study findings revealed that Strategic e-procurement practice explained 49.6% of the total variations in performance of devolved systems of government in Kenya. Further, results indicate that the overall model was statistically significant as supported by a p value of 0.000. This was supported by an F statistic of (F=155.245, p<0.05) and the reported p value (0.000) which was less than the conventional probability of 0.05 significance level. The standardized regression coefficient for Strategic E-procurement was 0.704. This indicates that a unit increase in the Strategic E-procurement would result in 70.4% increase in the performance of Devolved systems of government in Kenya this implied that there is a strong positive relationship between Strategic E-procurement and performance of Devolved systems of government in Kenya . Unique contribution to theory, practice and policy: Based on the findings, the study recommends that devolved systems of government should adopted e-procurement system and automate all procurement operation procedures to enhance smooth work flow and hence improve efficiency the study further recommends that Devolved systems of government should adopt e-procurement for various uses such as in the standardization of services for representation in the catalog, sourcing goods and services globally, as way of reducing costs in areas such tendering processes, payment and contract management. But management should be aware and cautious that e-procurement is capital intensive in terms of acquisition and laying down the required infrastructure and highly perishable. Thus the study recommends that strategic e-procurement practice should be implemented within the legal framework of public procurement acts and regulations because it moderate has positive correlation with the performance of Devolved systems of government in Kenya. The findings are in harmony with technology acceptance model which suggest that emerging technologies cannot improve organizational effectiveness and performance if the change has not been accepted by the users. Therefore first it's crucial for the users to accept the new technology (e-procurement) so as to reduce administrative costs, possible broadening of suppliers' base, and easy access to preferred goods. In conclusion technology acceptance model can be used by future scholars.